Trash crisis on earth - Stadler, Alexander (Stadler, Alexander. Julian Rodriguez, 2008)
Eight-year-old Julian Rodriguez escapes from the crisis of the moment (being sent to his room for not taking out the trash) by imagining he's a space warrior.